Steric and Electronic Factors Affecting the Conformation of Bimetallic CuI Complexes: Effect of the Aliphatic Spacer of Tetracoordinating Schiff‐Base Ligands. Issue 52 (21st August 2018) - Díaz, Daniel E.; Llanos, Leonel; Arce, Pablo; Lorca, Romina; Guerrero, Juan; Costamagna, Juan; Aravena, Daniel; Ferraudi, Guillermo; Oliver, Allen; Lappin, A. Graham; Lemus, Luis
Abstract: A family of six homoleptic [Cu I (L n )]2 (ClO4 )2 and six heteroleptic [Cu I (L n )(PPh3 )2 ]2 (ClO4 )2 bimetallic complexes, in which L n are bis‐Schiff base ligands with alkyl spacers of variable length ( n =2–7 −CH2 −), were prepared to evaluate the role of the spacer on the formation of helicates or mesocates. In the homoleptic series, spectroscopic and theoretical studies indicate that preferences for a conformation are based on energetic parameters, mainly, the establishment of noncovalent interactions. The odd–even nature of the spacers preconditions the superposition of the aromatic rings to allow the juxtaposition necessary for noncovalent interactions, whereas the increase of the length reduces the strength of such interactions. Consequently, complexes with even‐spacers of short length were identified as helicates in solution, [Cu I (L n )]2 2+ ( n =2, 4). Complexes [Cu I (L n )]2 2+ ( n =3–7) dissociate in solution to produce the monometallic complexes in equilibrium, [Cu I (L n )] + . The stability of the bimetallic species is discussed in terms of their conformations. The set of heteroleptic complexes was prepared to evaluate the reach of the "odd–even rule" in the solid, which is based on the "zig–zag" arrangements of the spacers. Based on crystallographic information, "S‐" and "C"‐type conformations of L n are related to even and odd spacers, respectively. This trend is considered in addition to other factors to explain preferences for either a mesocate or helicate conformation in the homoleptic series. Abstract : Size does matter : Both the odd–even nature and length of the alkyl spacers in a series of bimetallic Cu I complexes determine the preference for a helicate or a mesocate conformation. In even‐spaced ligands of short length ( n =2 and 4), the establishment of noncovalent interactions stabilizes the helical conformation (see scheme).